2016
DOI: 10.1038/bmt.2016.77
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of serum cytokine profile after hematopoietic stem cell transplantation in systemic sclerosis patients

Abstract: Abbreviations: IFN = interferon; IL = interleukin; MCP = monocyte chemoattractant protein; SSc = systemic sclerosis; TGF = transforming growth factor; VEGF = vascular endothelial growth factor. a Values were obtained in 8 SSc patients only. b Values were obtained in 16 SSc patients only. Serum cytokine levels are presented as mean ± s.e. NS with P40.05.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 14 publications
1
16
0
4
Order By: Relevance
“…The serum proteins correlating with the IFN and neutrophil transcript modules, as well as several Th2/M2 macrophage (PARC (CCL-18), IL-6, MCP-1 (CCL-2)) cytokines, also decreased significantly after the HSCT while there was no significant change in the CYC arm. Consistent with our findings, serum MCP-1, a prominently dysregulated cytokine in SSc,21 significantly decreased after treatment in 20 individuals with SSc undergoing HSCT in the multicentre European ASTIS study 33. Paralleling the transcript-level findings, these results confirm significant changes in the serum protein signatures of SSc after HSCT.…”
Section: Discussionsupporting
confidence: 90%
“…The serum proteins correlating with the IFN and neutrophil transcript modules, as well as several Th2/M2 macrophage (PARC (CCL-18), IL-6, MCP-1 (CCL-2)) cytokines, also decreased significantly after the HSCT while there was no significant change in the CYC arm. Consistent with our findings, serum MCP-1, a prominently dysregulated cytokine in SSc,21 significantly decreased after treatment in 20 individuals with SSc undergoing HSCT in the multicentre European ASTIS study 33. Paralleling the transcript-level findings, these results confirm significant changes in the serum protein signatures of SSc after HSCT.…”
Section: Discussionsupporting
confidence: 90%
“…Thereafter, Tsukamoto et al found persistent inversion of the Th2/Th1 ratio in eleven SSc patients until 3 years post-aHSCT [12]. In a pilot study, we reported restoration of Tregs and their suppressive function 2 years after aHSCT in seven SSc patients compared to controls [13], and partial fall of the pre-transplant increase in pro-fibrotic and Th2-cytokines serum levels [14]. Several questions remain, such as which of the post-transplant IR mechanisms are most relevant to warrant prolonged remission and what is the duration of the immunological transplant-induced effects?…”
Section: Introductionmentioning
confidence: 93%
“…The first study analyzed the serum levels of inflammatory cytokines (IL-2, IL-6, IL-8, and IFN-γ), pro-fibrotic molecules (TGF-β, IL-4, and PDGF), pro-angiogenic factors (VEGF and PDGF), endothelial markers (E-selectin and P-selectin) and MCP-1 chemokine before and up to 4 years after HSCT in 20 SSc patients. Even though a decrease in IL-2 and IL-8 levels, along with a slight but significant decrease in TGF-ß levels after 6 months has been demonstrated, these fluctuations did not reflect the skin score improvement after AHSCT ( 53 ).…”
Section: Immunologic Mechanisms Of Ahsctmentioning
confidence: 98%